Adaptive functional reorganization in amyotrophic lateral sclerosis: coexisting degenerative and compensatory changes. (13th August 2019) - Abidi, M.; de Marco, G.; Couillandre, A.; Feron, M.; Mseddi, E.; Termoz, N.; Querin, G.; Pradat, P. ‐F.; Bede, P.
Abstract : Background and purpose: Considerable functional reorganization takes place in amyotrophic lateral sclerosis (ALS) in face of relentless structural degeneration. This study evaluates functional adaptation in ALS patients with lower motor neuron predominant (LMNp) and upper motor neuron predominant (UMNp) dysfunction. Methods: Seventeen LMNp ALS patients, 14 UMNp ALS patients and 14 controls participated in a functional magnetic resonance imaging study. Study‐group‐specific activation patterns were evaluated during preparation for a motor task. Connectivity analyses were carried out using the supplementary motor area (SMA), cerebellum and striatum as seed regions and correlations were explored with clinical measures. Results: Increased cerebellar, decreased dorsolateral prefrontal cortex and decreased SMA activation were detected in UMNp patients compared to controls. Increased cerebellar activation was also detected in UMNp patients compared to LMNp patients. UMNp patients exhibit increased effective connectivity between the cerebellum and caudate, and decreased connectivity between the SMA and caudate and between the SMA and cerebellum when performing self‐initiated movement. In UMNp patients, a positive correlation was detected between clinical variables and striato‐cerebellar connectivity. Conclusions: Our findings indicate that, despite the dysfunction of SMA–striatal and SMA–cerebellar networks, cerebello‐striatal connectivity increases in ALS indicative of compensatory processes. The coexistence of circuits with decreased and increased connectivity suggests concomitant neurodegenerative and adaptive changes in ALS.